Gérer les temps pour gérer la qualité : l’activité de traitement des dossiers de retraite - Valérie Zara-Meylan; Serge Volkoff (Activités)
This paper aims to analyze the relation between the management of multiple temporal frameworks in a case file processing activity and the quality of the service. This research is based on an analysis of the activity of “Pension Advice Technicians” in a French organization responsible for handling the case files of beneficiaries - future pensioners - and managing relations with them. In these situations, the quality of service is conventionally measured through an array of indicators used to steer the services provided and control the work carried out. However, these indicators do not measure the full range of skills used by members of staff. Our research aims to understand the activity of the technicians and address its temporal complexity in order to show how they ensure the quality of the service they provide in broader dimensions. Our methodology was based on an ergonomic analysis of the activity, adopting a holistic approach to the work and its challenges. It examines the dynamic management of their temporal frameworks, firstly within the working day and then more transversally in career regularization, appointment sets and management of "errors" returned by the Control. This profession, which requires high levels of administrative rigor, also requires an ability to manage the multiple dynamics involved, including the relationships the technicians establish with the beneficiaries themselves, as well as with the internal control bodies. From an ergonomics perspective, the aim is to ensure that the working methods do not ignore the need to construct and mobilize these temporal skills through experience, as this would be detrimental to the quality, but instead that they support their development. The issue of work system quality is then how to best support temporal framework management, taking into account the individual and collective activity and the resolution of temporal dilemmas inherent in the work.